The long-run and short-run impacts of investment, export, money supply, and inflation on economic growth in Indonesia - Erni Panca Kurniasih (Universitas Hayam Wuruk Perbanas, 2019)
The development of investment and export in Indonesia as well as money supply shows an increase, while the inflation rate shows a decline. Yet, this is not always followed by the increase of economic growth. This study aims to explain the relationship between investment, export, money supply and inflation with the economic growth in Indonesia. It used time-series data from the first quarter in 2001 to the fourth quarter in 2014 and were analyzed using multiple regression models with Error Correction Model (ECM) and classical assumptions. It showed that in short-run, there are significant effects of investment and export on economic growth while money supply and inflation do not have significant effects. This study also found that in in long-run, there are significant effects of investment, export, money supply and inflation on the economic growth in Indonesia. Bank Indonesia should apply a tight money policy consistently to achieve the long-run inflation target